2016
DOI: 10.1186/s12879-016-1417-2
|View full text |Cite|
|
Sign up to set email alerts
|

Co-distribution and co-infection of chikungunya and dengue viruses

Abstract: BackgroundChikungunya and dengue infections are spatio-temporally related. The current review aims to determine the geographic limits of chikungunya, dengue and the principal mosquito vectors for both viruses and to synthesise current epidemiological understanding of their co-distribution.MethodsThree biomedical databases (PubMed, Scopus and Web of Science) were searched from their inception until May 2015 for studies that reported concurrent detection of chikungunya and dengue viruses in the same patient. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
192
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(199 citation statements)
references
References 77 publications
2
192
0
5
Order By: Relevance
“…More recently, Villamil-Gomez et al reported a 49-year-old male from Colombia with a febrile illness, bilateral conjunctivitis and a pruritic rash that was diagnosed with ZIKV, CHIKV and DENV and had an uneventful course [37]. The true extent of CHIKV-DENV co-infection has been hampered by current diagnosis largely based on clinical grounds with unavailability of molecular methods in many parts of the world [38], [39].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Villamil-Gomez et al reported a 49-year-old male from Colombia with a febrile illness, bilateral conjunctivitis and a pruritic rash that was diagnosed with ZIKV, CHIKV and DENV and had an uneventful course [37]. The true extent of CHIKV-DENV co-infection has been hampered by current diagnosis largely based on clinical grounds with unavailability of molecular methods in many parts of the world [38], [39].…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion of dengue is more important than establishing chikungunya virus infection during febrile periods, as patients may require nonsteroidal anti-inflammatory drugs (NSAIDs), which is not advocated during dengue infection [3]. Not only that, dengue has a higher mortality (0.5-3.5%) than chikungunya (<0.1%) and simultaneous infections by both viruses may result in serious disease though controversies exist [1].…”
Section: Discussionmentioning
confidence: 99%
“…Dengue is endemic and chikungunya is an emerging infection in Bangladesh [1][2][3]. Since both the viruses are transmitted by Aedes mosquitoes, simultaneous or sequential infections by chikungunya and dengue viruses are not impossible.…”
Section: Introductionmentioning
confidence: 99%
“…After publication of the original article [1], it came to the authors' attention that there were errors within Fig. 1 and Additional file 1.…”
Section: Erratummentioning
confidence: 99%